Exploration of genetically determined resistance against hepatitis C infection in high‐risk injecting drug users. Issue 8 (26th February 2014) - Sugden, P. B.; Cameron, B.; Luciani, F.; Lloyd, A. R.; the HITS investigators
Summary Genetic resistance to specific infections is well recognized. In hepatitis C virus (HCV) infection, genetic polymorphisms in IL‐28B and the killer cell immunoglobulin‐like receptors (KIR) and their HLA class I ligands have been shown to affect clearance of the virus following infection. There are limited data regarding resistance to established HCV infection. Reliable quantification of repeated exposure in high‐risk populations, such as injecting drug users (IDU), is a key limitation of previous studies of resistance. Behavioural data and DNA from IDU (n = 210) in the Hepatitis C Incidence and Transmission Study in prisons (HITS‐p) cohort were genotyped for polymorphisms in: IL‐28B, peptidyl‐prolyl isomerase A (PPIA), HLA‐C and KIR2. To quantify risk, a composite risk index based on factors predictive of incident HCV infection was derived. Logistic regression analysis revealed the risk index was strongly associated with incident HCV infection (P < 0.0001). The upper tertile of the uninfected individuals had risk indices comparable to the incident cases, but remained uninfected. There were no significant differences in the frequencies of IL‐28B or PPIA polymorphisms between these exposed‐uninfected cases, or in the frequencies of KIR2‐DL3, HLA‐C1, or their combination. A framework for the investigation of genetic determinants of resistance to HCV infection has been developed. Several candidate gene associations were investigated and excluded. Further investigation of genetic determinants of resistance to HCV infection is warranted.